2021
DOI: 10.1242/dev.199919
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis stomatal polarity protein BASL mediates distinct processes before and after cell division to coordinate cell size and fate asymmetries

Abstract: In many land plants, asymmetric cell divisions (ACDs) create, and pattern differentiated cell types on the leaf surface. In the Arabidopsis stomatal lineage, BREAKING OF ASYMMETRY IN THE STOMATAL LINEAGE (BASL) regulates ACD division plane placement and cell fate enforcement. Polarized subcellular localization of BASL is initiated before ACD and persists for many hours after the division in one of the two daughters. Untangling the respective contributions of polarized BASL before and after division is essentia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Previously, we identified CONSTITUTIVE TRIPLE RESPONSE1 ( CTR1) as a positive regulator of meristemoid proliferation (Gong, Alassimone, Varnau, et al, 2021), although the detailed mechanism underlying this effect was unknown. Notably, Vaseva et al (2018) reported that epidermal cell expansion was inhibited in the ctr1 mutant, leading us to investigate whether the lack of cell expansion and consequently, a reduction in cell size, could trigger premature differentiation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we identified CONSTITUTIVE TRIPLE RESPONSE1 ( CTR1) as a positive regulator of meristemoid proliferation (Gong, Alassimone, Varnau, et al, 2021), although the detailed mechanism underlying this effect was unknown. Notably, Vaseva et al (2018) reported that epidermal cell expansion was inhibited in the ctr1 mutant, leading us to investigate whether the lack of cell expansion and consequently, a reduction in cell size, could trigger premature differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Previously reported mutants and transgenic lines include: pSPCH∷SPCH-YFP pATML1∷RCI2A-mCherry in spch-3 (Lopez-Anido et al, 2021), pMUTE∷MUTE-YFP pATML1∷RCI2A-mCherry (Davies & Bergmann, 2014), pBRXL2∷BRXL2-YFP pATML1∷RCI2A-mCherry (Gong, Varnau, et al, 2021; Rowe et al, 2019), pBRXL2∷BRXL2-YFP pATML1∷RCI2A-mCherry in ctr1 (Gong, Alassimone, Varnau, et al, 2021), tetraploid Col-0 (Robinson et al, 2018), p35S∷PIP2A-RFP in basl-2 (Rowe et al, 2019), pBRXL2∷BRXL2-YFP pATML1∷RCI2A-mCherry in myoxi-i (Muroyama et al, 2020), pATML1∷mCherry-RCI2A pBASL∷BRX-CFP (Rowe et al, 2019), and pATML1∷H2B-mTFP pATML1∷mCit-RCI2A (Robinson et al, 2018). We created crwn1-1 pATML1∷H2B-mTFP pATML1∷mCit-RCI2A by crossing crwn1-1 (Dittmer et al, 2007) with pATML1∷H2B-mTFP pATML1∷mCit-RCI2A (Robinson et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After it is inherited by the SLGC through the ACD, cortical BASL/BRXf enhances MITOGEN ACTIVATED PROTEIN KINASE (MAPK) signaling to suppress meristemoid identity ( 15, 17 ). Despite its central role in coordinating ACD entry and daughter-cell identity post-division ( 18 ), how BASL/BRXf asymmetric inheritance is regulated is unknown (Fig. 1A).…”
Section: Main Textmentioning
confidence: 99%